PENGARUH MEDIA SOSIAL TERHADAP KESEJAHTERAAN PSIKOLOGIS REMAJA SEKOLAH MENENGAH DI INDONESIA - Rohmatillah, Nely; Qomaruddin, Qomaruddin; Ahmad, Nur Fatih; Fadhilah, Nilna Fatih (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
The use of information technology and social media among teenagers is a major concern in their psychological context. This research applies literature study methods to investigate the impact of social media use on the psychological well-being of adolescents. Based on data from the Ministry of Communication and Information (Kominfo), Indonesian teenagers are highly exposed to social media, with 79.5 percent of them being internet users. Social media has become integral to teenagers' daily lives, playing an important role in communication, social interaction, and the search for identity. This study focuses attention on aspects of anxiety and depression as indicators of adolescent psychological well-being. Research results suggest that excessive social media use, exposure to cyberbullying, and social comparison may contribute to increased levels of anxiety and depression. The literature study method is used to detail the influence of social media on teenagers, exploring information from various related literature sources. Additionally, this study identified moderating factors, such as offline social support and regulation of social media use, that influence the complexity of the relationship between social media and adolescents' psychological well-being.